Raingauge Density for Small Watershed - Ullah, Wasi; Gupta, S. K.; Babu, Ram; Nayal, M. S. (Indian Forester, 1969)
Determination of areal rainfall amount is essential to most hydrologic investigations. To measure 'true' rainfall, various raingauge installed at a density of 1.94 to 39.80 hectares per raingauge, at Soil Conservation Farm, Dehra Dun have shown that the variation in each storm recorded in 5 years (comprising 137 storms of more than 10.0 mm) was within '5 percent level of significance' and therefore one raingauge up to watershed area of 370 hectares is sufficient. In case the subwatersheds within this size large watershed, are gauged, one raingauge for each subwatershed may be installed as for taking more details. Further studies to determine rain gauge density for larger areas than 370 hectares are required to be conducted under local condition.